Impact of controllability on pain and suffering - Löffler, Martin; Kamping, Sandra; Flor, Herta (Pain reports, 2018)
Introduction: Chronic pain and pain-related suffering are major health problems. The lack of controllability of experienced pain seems to greatly contribute to the extent of suffering. This study examined how controllability affects the perception of pain and pain-related suffering, and the modulation of this effect by beliefs and emotions such as locus of control of reinforcement, pain catastrophizing, and fear of pain. Methods: Twenty-six healthy subjects received painful electric stimulation in both controllable and uncontrollable conditions. Visual analogue scales and the “Pictorial Representation of Illness and Self Measure” were used to assess pain intensity, unpleasantness, pain-related suffering, and the level of perceived control. We also investigated nonverbal indicators of pain and suffering such as heart rate, skin conductance, and corrugator electromyogram. Results: Controllability selectively reduced the experience of pain-related suffering, but did not affect pain intensity or pain unpleasantness. This effect was modulated by chance locus of control but was unrelated to fear of pain or catastrophizing. Physiological responses were not affected by controllability. In a second sample of 25 participants, we varied the instruction. The effect of controllability on pain-related suffering was only present when instructions focused on the person being able to stop the pain. Discussion: Our data suggest that the additional measure of pain-related suffering may be important in the assessment of pain and may be more susceptible to the effects of perceived control than pain intensity and unpleasantness. We also show that this effect depends on personal involvement.